The Influence of Capital and Prices on Frozen Food Business Profits in Kendari City - Inna, Nisrina Uswatun Husna; Idrus Salam; Sadimantara, Fahria Nadiryati (International journal of technology and education research, 2023)
Capital and the determination of the price of a product have an effect on every business actor, especially in setting the price of the product to be sold. This is because if the price of products sold, such as frozen processed food, increases in price from the previously set price, then there will be a decrease in consumer interest. This study aims to determine the effect of capital and price on the profits of frozen food businesses in Kendari City. The type of data used is qualitative data while the data collection techniques used in this study are direct interview and documentation techniques. Data analysis used in this study is multiple linear regression analysis. The results of the study show that the effect of capital and price on the profits of the frozen food business in Kendari City indicates that the variables of capital and prices have a simultaneous or joint effect on the profits of the frozen food business in Kendari City. From the results of the t analysis, the capital variable (X1) has no significant effect on business profits (Y). Capital is not the only factor that has an important influence because as an entrepreneur, in the case of a frozen food entrepreneur, you do not have to have large capital in the form of money that can help generate business profits. Meanwhile, from the results of the t-count analysis, the price variable (X2) has a real or significant effect on the profits of the frozen food business in Kendari City.